Bidyāsāgara smrti - De, Biśvanātha (Sāhityam, 1979)
On the life and works of the Bengali educationist, social reformer, and philanthropist Iswar Chandra Vidyasagar, 1820-1891; collection of writings and reminiscences by Bengali authors and close associates of Vidyasagar.